'Authoring' terrorism in Aziz Saâdallah's Le Temps du terrorisme. Issue 3 (3rd July 2019) - Petty, Sheila
Abstract: This essay explores how the Moroccan film Le Temps du terrorisme uses the frame of the artistic/creative process to stage a study of religious fanaticism and its tragic consequences. Drawing on melorealism, the filmmaker uses tropes of comedy and farce already familiar to his theatre and television audiences, but he also layers his text with self-reflexive strategies of direct address and narrator as witness. These devices work to bridge the distance between fiction and reality, and author and audience. As filmmaker, Aziz Saâdallah forges a personal relationship between artist and viewer and carves out a space for a dialectics of the artistic process: demanding an active audience, posing questions and forcing the viewer to think. He thus seeks to raise debate across a wide range of spectators and poses complex questions of responsibility, tolerance and the role of artistic expression in the present-day times of terrorism.